Upaya Mengatasi Golput pada Pemilu 2014 - Evelina, Lidya Wati; Angeline, Mia (Bina Nusantara University, 2015)
Data from General Election Commission (KPU) said the 2009 election abstentions level is still relatively high , ie 49,212,161 non voters (29.1%) of the 176,411,434 voters. The low political participation of Indonesian society is caused by many cases convoluting political parties, the lack of potential figure of political parties, and the decline of the party's image. Research aims to find the 2014 election socialization efforts of the General Election Commission to reduce the level of abstentions and how the media shape public opinion to reduce the abstentees. Research used qualitative method with data collection through interview and literature. Data were analyzed with data reduction and triangulation. The study found the socialization media used for 2014 election were national and regional media socializing to various schools and universities in Indonesia. KPU also recruited agents of socialization in 2014, put up posters and banners, did activities along with agents of socialization, and increased the number of polling stations (TPS). KPU disseminated the information to the mass media to be publicized. The goal is to involve the community and to contribute to the success of the election. Electronic mass media need to make a program that helps the socialization of the election, for example having an open debate of all parties participating in the election in a special slot provided by the government then they explain the program and their pro-people commitments. As conclusions, the commission and the media have not been systematically designing programs that can persuade public to participate in the election of 2014. Research recommends the media to make a program that is interactive and engaging based on local tastes and culture to provide a common understanding about the 2014 election.